The Influence of Financial Compensation, Work Facilities, and Workload on Employee Job Satisfaction - Abdul Rachman; Kuswandi Kuswandi; Sri Rahayu (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Job satisfaction plays a crucial role in enhancing employee productivity and efficiency. High job satisfaction motivates employees to perform better, while dissatisfaction can lead to decreased motivation and performance. Companies must consider factors that contribute to job satisfaction to foster a harmonious work environment. This study analyzes the impact of financial compensation, work facilities, and workload on employee job satisfaction at PT. Cakrawala Cemerlang Box in Mojokerto. Using a quantitative approach with a correlational research design, the study involved 36 office employees as participants. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression. The results indicate that financial compensation, work facilities, and workload each have a significant effect on employee job satisfaction, both individually and collectively. With a determination coefficient of 78.5%, these three factors account for the majority of variations in job satisfaction. In conclusion, increasing financial compensation, ensuring adequate work facilities, and implementing effective workload management significantly enhance employee job satisfaction. This highlights the importance of corporate strategies in managing these aspects to support employee performance and well-being.